Extrarenal angiomyolipoma in uterine cervix: rare presentation in unusual site - Monteiro, Rashmi; Sharma, Shikha; Gupta, Sonal; Choudhary, Indu (International Journal of Research in Medical Sciences, 2019)
Angiomyolipoma is a benign neoplasm composed of variable admixture of blood vessels, smooth muscle cells and adipose tissue. Cervical angiomyolipoma are extremely rare and to the best of our knowledge only five cases of angiomyolipoma in cervix have been reported in the literature till date. Authors are presenting a case of angiomyolipoma arising from the uterine cervix. 43 years old female presented with mass descending per vagina for 6 months. This case had no association with tuberous sclerosis. Microscopic examination showed an ill-defined polypoidal, non-encapsulated lesion covered by keratinized stratified epithelium. The lesion is made up of three components, predominantly by fascicles of spindle shaped cells, varying sized blood vessels and multiple foci of mature adipocytes with no evidence of atypia or increased mitotic activity. Smooth muscle component showed strong immunoreactivity to SMA and absence of elastic fibres in the blood vessels were confirmed by histochemistry. Non-vascular smooth muscle cells were negative for HMB-45 in contrast to renal and other extra-renal angiomyolipoma in which HMB-45 immunoreactivity in seen in these cells. To conclude, the differential diagnosis of lower abdominal mass and dysfunctional uterine bleeding should include the angiomyolipoma, even though the uterine cervix is an extremely rare location where they occur.